2020
DOI: 10.1177/0033354920968805
|View full text |Cite
|
Sign up to set email alerts
|

What Strategies Are Hospitals Adopting to Address the Opioid Epidemic? Evidence From a National Sample of Nonprofit Hospitals

Abstract: Objectives Hospitals are on the front lines of the opioid epidemic, seeing patients who overdose or have complicated infections, but the extent of services offered or whether services are evidence-based is not known. The objective of our study was to assess the extent to which nonprofit hospitals are addressing opioid abuse, a critical public health issue, through their community benefit work and to identify which evidence-based strategies they adopt. Methods We reviewed community benefit documents from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…For example, empirical evidence suggests that prolonged drug use may result in impaired volitional control [47]. Additionally, there are currently no evidence-based pharmaceutical treatments for those with stimulant use disorders [48] and many acute care facilities still do not provide patients with opioid use disorders evidence-based medication treatment or harm reduction interventions [49]. Clinicians therefore should be educated and encouraged to engage patients with previous or active injection drug use in non-stigmatizing and factual conversations about reducing harms associated with drug use, including the potential risks of injecting into VADs [15,50].…”
Section: Discussionmentioning
confidence: 99%
“…For example, empirical evidence suggests that prolonged drug use may result in impaired volitional control [47]. Additionally, there are currently no evidence-based pharmaceutical treatments for those with stimulant use disorders [48] and many acute care facilities still do not provide patients with opioid use disorders evidence-based medication treatment or harm reduction interventions [49]. Clinicians therefore should be educated and encouraged to engage patients with previous or active injection drug use in non-stigmatizing and factual conversations about reducing harms associated with drug use, including the potential risks of injecting into VADs [15,50].…”
Section: Discussionmentioning
confidence: 99%
“…7 More specific to the opioid epidemic, several studies have examined how NFPs have responded to the epidemic through their CB programs and the impact of Federal and State policies on NFPs' response to the epidemic. 7,[33][34][35][36][37] One study found that in urban communities most affected by the opioid epidemic NFPs address it by providing additional treatment capacity. Another study found that NFPs may prefer to support opioid treatment either in primary care or in formal treatment services rather than initiate treatment in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…33 The authors also found that state policies focused on opioid use disorder may be effective in nudging hospitals to expand their portfolio of interventions to address the opioid epidemic beyond their area of expertise, including harm reduction. 33,35 Another study found both institutional (eg, lack of resources) and community-level factors (eg, poverty rate) are associated with the decision of NFPs not to address opioid use disorder even after having identified it as a community need in their CHNAs. 36 The authors conclude that policies supporting NFP-LHD partnerships may assist NFPs in addressing community needs that fall outside their expertise to include the social and economic determinants of the opioid epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, to date, no safer alternative with equal analgesic efficacy to opioids has been found ( Stuart et al, 2018 ). Many other proposed strategies involve reducing opioid dosage by locally targeting injured tissue (and limit central penetration), or reducing opioid prescriptions including establishing multimodal pain treatment regimens (as opposed to opioid monotherapy), opioid prescription monitoring, and restricted prescribing guidelines ( Saloner et al, 2018 ; Mir et al, 2019 ; Franz et al, 2021 ). Yet this has not been enough.…”
Section: Introductionmentioning
confidence: 99%